Oceanic redox evolution in an early Cambrian intrashelf basin, South China - Yuyue Han; Meng Cheng; Jianbo Chen; Thomas J. Algeo; Bo Ran; Mengchun Cao; Zihu Zhang; Haiyang Wang; Dasheng Zhao; Tao Dong; Feng Wang; Taiping Huang; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Inverse identification of wind turbine horizontal thrust on steel-concrete hybrid tower using intelligent algorithm - Shou-Zhen Li; Yu-Hang Wang; Jinjin Wang; Ran Deng; Chao Hu; Liming Jiang (Engineering Structures, 2026)

Molecular Mechanism of Absorption, Transport and Metabolic Transformation of Astaxanthin in Aquatic Animals - Huakang Peng; Yihui Du; Qianwen Ding; Dongdong Du; Ruyue Dong; Chao Ran; Zhen Zhang; Yuanyuan Yao; Hui Liang; Ming Li; Nan Wang; Yalin Yang; et al. (Reviews in Aquaculture, 2026)
The global astaxanthin market reached $1.69 billion in 2024, with 47% directed to aquafeed—yet the molecular basis of its absorption, metabolism, deposition, and storage in aquatic organisms remains incompletely resolved. A deeper understanding of these mechanisms will help optimize feed formulations, enhance astaxanthin bioavailability, and improve economic efficiency in aquaculture. This study investigates the absorption mechanisms of astaxanthin mediated by intestinal lipid transporters (SR‐B1, CD36, NPC1L1) and its utilization/deposition in different tissues and organs. It reviews the latest research progress on major absorption pathways, metabolic processes, and storage forms of astaxanthin in aquatic organisms, analyzes key factors affecting its utilization efficiency, and discusses potential future research directions to provide a scientific basis and theoretical support for aquaculture practices.

Microbe-mediated coupling of soil disease suppression and rhizobial symbiosis in legume diversified cropping systems - Xiang-Yu Zhang; Rui Yuan; Xue Guo; Wen-Xue Zhang; Hao-Ran Li; Cao-Yue Wu; Jun-Yu Zhao; Ting-Ting Zhang; Hong-Wei Wang; Ricardo A. R. Machado; Stefan Scheu; Yong Jia; et al. (Plant and Soil, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

C10–C12 aromatics dominate ozone and secondary organic aerosol formation potential in emissions from printed circuit board manufacturing - Xiaodie Pang; Wei Song; Weiqiang Yang; Chao Peng; Jianqiang Zeng; Zhou Zhang; Xiao Tian; Hongcheng Lu; Xiangyu Zhang; Ran An; Yang Li; Runcheng Zhu; et al. (Journal of Environmental Sciences, 2026)

Hydrocarbon charging dynamics and its coupling with reservoir densification in a tight sandstone system: Insights from the Jurassic of the Yangxia Sag, Kuqa Depression - Chang-chao Chen; Jun Li; Jinz-hou Wang; Ling Li; Hao-ran Gao; Zheng-lian Pang; Xiu-yan Chen; Min Yang (Applied Geophysics, 2026)

Nine previously undescribed immunosuppressive ent-labdane diterpenoids from the roots of Eurysolen gracilis - Lin-Lin Teng; Yan-Chun Liu; Chao-Jiang Xiao; Shu-Xi Jing; De-Sen Li; Ran Xu; Xiao-Nian Li; Yan Liu; Sheng-Hong Li (Phytochemistry, 2026)

Cellular copper overload mediates senescence-associated secretory phenotype induction in BV2 microglia following lead and copper exposure - Tao Wang; Chao Chen; Ran Li; Li-Hong Su; Hao-Jie Tian; Hui-Jing Wang; Jia-Yi Xiong; Qing Dai; Di Wu; Gang Zheng (Food and Chemical Toxicology, 2026)

A chimeric PRRSV vaccine with dual Nsp2 deletions elicits cross-lineage protection against heterologous challenge - Zhuo-ran Miao; Bo Han; Ling-zhai Meng; Zhen-hui Ren; Yi-han Lu; Jing Li; Wen Sun; Shi-qin Zhang; Jia Wang; Jin-jin Ma; Jia-Lu Li; Yu-tong Zhu; et al. (The Veterinary Journal, 2026)

Beyond magnetic-field enhanced peroxymonosulfate activation: Interfacial restructuring of nanoscale Fe0 for efficient contaminant degradation - Jingyang Luo; Ran Yu; Xinyi Liu; Chao He; Fuqiang Liu; Jianglei Xiong; Shilong Jiang; Song Cheng; Yiping Li (Chemical Engineering Journal, 2026)

Animal gut microbes and microbiomes in the 21st century and beyond - Zhigang Zhang; Feng Jiang; Zhipeng Li; Limei Lin; Bin Qi; Dandan Han; Chao Ran; Shengyong Mao; Junjun Wang; Zhigang Zhou; Min Wang; Jilian Li; et al. (Science China Life Sciences, 2026)
Animal gut microbiomes—comprising bacteria, archaea, fungi, viruses, and protozoa—are fundamental to host evolution, physiology, and ecosystem resilience. This review synthesizes 21st-century advances in their diversity, spatiotemporal dynamics, and functional roles across the animal kingdom. Although high-throughput metagenomics has transformed the field, major biases remain: most studies still focus on domesticated vertebrates and fecal samples, leaving substantial “microbial dark matter” in wild hosts, invertebrates, and non-bacterial domains unexplored. We highlight how gut microbiomes mediate adaptation to environmental extremes, including hypoxia, temperature stress, and toxins, and how industrialization disrupts these communities, contributing to biodiversity loss and disease risk. We further integrate eco-evolutionary theory, multi-omics, and spatial modeling to clarify cross-kingdom interactions and functional networks. Finally, we discuss translational applications—including probiotics, fecal microbiota transplantation (FMT), phage therapy, and synthetic consortia—and emphasize the need for global collaborative initiatives, artificial intelligence (AI)-driven discovery, and standardized databases to unlock the full potential of animal gut microbiomes for biodiversity conservation, climate resilience, and planetary health in the coming decades.

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Integrated metabolomic and transcriptomic analyses unravel the function of quercetin in enhancing grape resistance to anthracnose - Meng-Fei Li; Ming-Yi Wang; Fu-Lai Han; Zhe Zhang; Ya-Lin Liu; Meng-Ran Li; Yu-Fei Li; Jie Yang; Xin Liu; Guang-Chao Liu (Postharvest Biology and Technology, 2026)

An improved ion-exchange-to-silver-salt procedure for δ18O measurement of nitrate in natural samples - Bo Wang; Chao Li; Ying Wang; Linbao Chen; Yuting Wang; Ran Ma; Zhengyu Zhu; Youping Zhou (Analytica Chimica Acta, 2026)

Integrative analysis of DEHP exposure and prostate cancer: Mechanistic insights and predictive modeling - Wen-Cai Zheng; Wen-Tao Xu; Chao-Ran Chen; Fei Lin; Shao-Hao Chen; Xiao-Dong Li; Xiong-Lin Sun; Qing-Shui Zheng; Yong Wei; Xue-Yi Xue; Zhi-Bin Ke; Ning Xu (Environmental Pollution, 2026)

Copper-based drugs inhibit infectious bronchitis virus (IBV) in vitro and in vivo - Lisen Lin; Jiaqi Li; Chao Shang; Dapeng Li; Mingzhe Sun; Gaojie Song; Guangbo Qu; Xiao Li; Ran Zhu; Cuiling Zhang; Qinghao He; Guibin Jiang (Veterinary Microbiology, 2026)

Numerical study on the influence of submerged breakwater slope on wave-current propagation behaviors - Hong-Fei Mao; Long Han; Kai-Lin Chen; Ying-Chao Ma; Jin-Bo Lin; Zheng-Lin Tian; Zhong-Bing Zhou; Ran Ji; Yan-Li He; Li-Min Wang (Ocean Engineering, 2026)

Close-packed metal organic frameworks enabled high-energy solid-state lithium metal batteries - Yining Zhang; Hongsheng Shi; Yuyao Zhang; Xin Chen; Shuanghong Wang; Jinjiang Liang; Qiong Yuan; Tianyi Gao; Ran Wei; Haochen Zhang; Tao Li; Tianquan Lin; et al. (Chemical Engineering Journal, 2026)

Application, challenges, and opportunities of organic metal frameworks materials in oil-water separation - Jiahao Liao; Bingfan Li; Longfei Ran; Jiang Han; Chao Yang; Zhijun Li; Tifeng Jiao (Journal of Environmental Chemical Engineering, 2025)

Moderate-intensity aerobic exercise inhibits cell pyroptosis to improve myocardial ischemia-reperfusion injury - Yu Wang; Yushan Li; Chaofan Chen; Hailong Zhang; Weili Liu; Chao Wu; Haonan Chen; Ran Li; Jinghan Wang; Yingchao Shi; Shengfang Wang; Chuanyu Gao (Molecular Biology Reports, 2025)

IGFBP7 and CCT2 are novel lactylation-driven mediators of endothelial-to-mesenchymal transition in idiopathic pulmonary fibrosis - Li Wenhao; Huang Ling; Fang Wanqing; Wang Wanrong; Cao Chao; Wang Ran (Functional & Integrative Genomics, 2025)

Recovery of siliceous ecosystems promoted Early Silurian climatic cooling - Huan Xu; Bo Ran; Terry T. Isson; Xinyang Chen; Chao Luo; Yi Li; Yiqing Zhu; Tong Sun; Yuyue Han (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Biochar and iron minerals facilitate the reduction of pollution and sequestration of carbon in chloramphenicol-contaminated soil under dry conditions - Pengfei Cheng; Junliang Chen; Ran Xu; Qin Tian; Xiaobo Luo; Zhicong Dai; Zhiliang Li; Yao Lu; Lianghui Li; Kuan Cheng; Chao Guo; Guanlin Li; et al. (Applied Soil Ecology, 2025)

A copper-based single-atom material effectively controls plant diseases with nearly zero soil residue and low phytotoxicity - Rui Huang; Yong Yan; Yafei Jiang; Chunyan Gu; Zhentao Ma; Lifang Xue; Yao Ma; Xingen Lin; Juan Zhang; Ran Shi; Yiwen Wang; Linjing Liu; et al. (Science Bulletin, 2025)

Preliminary study on ameliorative effects of P-Hydroxycinnamic acid on high-fat diet-induced injury in zebrafish - Qianyao Kuang; Delong Meng; Zhen Zhang; Xingyu Chen; Tsegay Teame; Hongwei Yang; Yalin Yang; Chao Ran; Yuanyou Li; Zhigang Zhou (Fish & Shellfish Immunology, 2025)

CCP domain containing protein from complement factor H of Paralichthys olivaceus has potential effects against Edwardsiella piscicida infection - Xuan-yue Wang; Yu-ting Du; Xin-yi Jiang; Zhuo-ran Ma; Chao-ran Zhang; Xue-peng Li; Zeng-zhi Yuan; Mo-fei Li (Aquaculture, 2025)

“Using waste straw to prevent pollution”: Enabling closed-loop design of chrome-free tanning agent with tanning-masking dual effect - Huaqing Liu; Taotao Qiang; Ran Zhang; Ruilong Li; Xin Sun; Sijie Yu; Chao Wu; Longfang Ren (Waste Management, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Strain-specific effects of fish originated Bacillus velezensis on growth, gut health, and disease resistance of zebrafish - Yuan-Yuan Yao; Wen-Hao Zhou; Juan Hu; Ya-Lin Yang; Ming Li; Rui Xia; Chao Ran; Zhen Zhang; Zhi-Gang Zhou (Fish & Shellfish Immunology, 2025)

TdCCA with Dual-Modal Signal Fusion: Degenerated Occipital and Frontal Connectivity of Adult Moyamoya Disease for Early Identification - Yuchen Ran; Yingwei Fan; Shuang Wu; Chao Chen; Yangxi Li; Tianxin Gao; Houdi Zhang; Cong Han; Xiaoying Tang (Translational Stroke Research, 2025)

Phage Therapy Enhances Survival, Immune Response, and Metabolic Resilience in Pacific White Shrimp (Litopenaeus vannamei) Challenged with Vibrio parahaemolyticus - Chao Zeng; Long Qi; Chao-Li Guan; Yu-Lin Chang; Yu-Yun He; Hong-Zheng Zhao; Chang Wang; Yi-Ran Zhao; Yi-Chen Dong; Guo-Fang Zhong (Fishes, 2025)
Acute hepatopancreatic necrosis disease (AHPND), caused by the bacterium Vibrio parahaemolyticus, is a major threat to global shrimp aquaculture. In this study, we evaluated the therapeutic effects of phage therapy in Litopenaeus vannamei challenged with AHPND-causing Vibrio parahaemolyticus. Phage application at various concentrations significantly improved shrimp survival, with the 1 ppm group demonstrating the highest survival rate. Enzymatic assays revealed that phage-treated shrimp exhibited enhanced immune enzyme activities, including acid phosphatase (ACP), alkaline phosphatase (AKP), and lysozyme (LZM). In addition, antioxidant defenses such as superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GSH-PX), and total antioxidant capacity (T-AOC) significantly improved, accompanied by reduced malondialdehyde (MDA) levels. Serum biochemical analyses demonstrated marked improvements in lipid metabolism, particularly reductions in triglyceride (TG), total cholesterol (TC), and low-density lipoprotein (LDL), alongside higher levels of beneficial high-density lipoprotein (HDL). Transcriptomic analysis identified 2274 differentially expressed genes (DEGs), notably enriched in pathways involving fatty acid metabolism, peroxisome functions, lysosomes, and Toll-like receptor (TLR) signaling. Specifically, phage treatment upregulated immune and metabolic regulatory genes, including Toll-like receptor 4 (TLR4), myeloid differentiation primary response protein 88 (MYD88), interleukin-1β (IL-1β), nuclear factor erythroid 2-related factor 2 (Nrf2), and peroxisome proliferator-activated receptor (PPAR), indicating activation of innate immunity and antioxidant defense pathways. These findings suggest that phage therapy induces protective immunometabolic adaptations beyond its direct antibacterial effects, thereby providing an ecologically sustainable alternative to antibiotics for managing bacterial diseases in shrimp aquaculture.

China’s marine plastic pollution governance path: focusing on the judicial positioning of PIL initiated by procuratorial agencies - Ben-Chao Fu; Chuan-Kai Guo; Xiu-Juan Li; Hai-Dong Cai; Jin-Hua Guo; He-Ran Li (Frontiers in Marine Science, 2025)
Can procuratorial agencies play a key role in China’s governance of marine plastic pollution (MPPG)? Within the current discussions about the legal framework of China’s MPPG, courts, marine environmental regulatory authorities, procuratorial agencies, and environmental protection organizations are typically seen as the main stakeholders. However, the role of procuratorial agencies, as the statutory entity for initiating PIL in marine environmental protection, has been significantly overlooked. This raises a range of questions including how should procuratorial agencies leverage their advantages in PIL to enhance the diversity of participants in the litigation process? What inherent challenges exist in marine environmental lawsuits? What substantive and procedural obstacles will procuratorial agencies face when engaging in MPPG-related litigation? This study argues that procuratorial agencies, by fulfilling their public interest litigation (PIL) function in marine environmental protection, can effectively improve MPPG governance. The study focuses on issues such as the unclear prerequisites for initiating MPPG-related lawsuits by procuratorial agencies, the criteria for selecting diverse litigation models, and the applicability of procuratorial agencies’ PIL in foreign-related cases.

Resolving the Snowball Earth conundrum: the role of marine dissolved organic carbon pool - Bing Shen; Xianguo Lang; Ruimin Wang; Yonggang Liu; Shihong Zhang; Tianzheng Huang; Xuelei Chu; Yixin Cui; Weiming Ding; Yuansheng Du; Ran He; Kangjun Huang; et al. (Science Bulletin, 2025)

Endophytic fungi promote peanut fitness by re-establishing rhizosphere nematode communities under continuous monocropping conditions - Xiang-Yu Zhang; Hao-Ran Li; Hui-Jun Jiang; Xiao-Han Wu; Chen-Yu Ma; De-Lin Luo; Wei Zhang; Chuan-Chao Dai (Plant and Soil, 2025)

A comprehensive omics resource and genetic tools for functional genomics research and genetic improvement of sorghum - Chengxuan Chen; Fengyong Ge; Huilong Du; Yuanchang Sun; Yi Sui; Sanyuan Tang; Zhengwei Shen; Xuefeng Li; Huili Zhang; Cuo Mei; Peng Xie; Chao Li; et al. (Molecular Plant, 2025)

Effects of plant aromas on stress recovery and brain activity in university students - Nan Zhang; Chao Liu; Yuying Ren; Wenxuan Li; Ran Chen; Weijun Gao (Building and Environment, 2025)

Predicting Persistent Aneurysm Filling After Pipeline Embolization Device Treatment in Patients with Intracranial Aneurysm: Development and External Validation of a Nomogram Model - Linggen Dong; Chao Wang; Xiheng Chen; Mingtao Li; Tong Li; He Liu; Yang Zhao; Ran Duan; Weitao Jin; Yukun Zhang; Yang Wang; Ming Lv (Translational Stroke Research, 2025)

A UDP-glucuronosyltransferase gene UGT379A1 involved in detoxification of lufenuron in Diaphorina citri - Ze-Hao Huang; Qi Pan; Zhen Wu; Yu-Chao Shen; Si-Chen Li; Qi-Qi Yang; Shao-Hui Zhang; Shuang Lei; Yang-Yang Cui; Li-Li Ding; Shi-Jiang Yu; Liu Liu; et al. (Pesticide Biochemistry and Physiology, 2025)

An amino-functionalized magnetic mesoporous silica nano-adsorbent for removing antibiotics from aqueous environments - Sihai Hu; Liuyan Tang; Rui Zhang; Ran Sun; Yuchen Zhang; Zhengcang Song; Yasong Li; Yaoguo Wu; Xujiang Chao; Yuezhou Zhang (Journal of Water Process Engineering, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Land use patterns change N and P cycling bacterial diversity in an acidic karst soil - Zhou Li; Wangfei Qin; Yongliang You; Jihui Chen; Xuechun Zhao; Rui Dong; Xinyao Gu; Song Cui; Chao Chen; Erinne Stirling; Ran Xue (Agriculture, Ecosystems & Environment, 2025)

A novel framework for dynamic and quantitative mapping of damage severity due to compound Drought–Heatwave impacts on tea Plantations, integrating Sentinel-2 and UAV images - Ran Huang; Yuanjun Xiao; Shengcheng Li; Jianing Li; Wei Weng; Qi Shao; Jingcheng Zhang; Yao Zhang; Lingbo Yang; Chao Huang; Weiwei Sun; Weiwei Liu; et al. (Computers and Electronics in Agriculture, 2025)

Effect of crowding stress on liver health, gut permeability and gut microbiota of genetically improved farmed tilapia (GIFT, Oreochromis niloticus) - Jian Zhang; Jie Chen; Hui Liang; Ming Li; Wenhao Zhou; Yalin Yang; Zhen Zhang; Qianwen Ding; Chao Ran; Zhigang Zhou (Aquaculture, 2025)

Dual-ion permeation Janus membrane-assisted element reconstitution system enables fluorosilicate-oriented recovery from fluoride-rich and silica-rich wastewaters - Yangbo Qiu; Chao Wang; Ran Li; Lidong Feng; Shuaijun Yu; Jiangnan Shen; Long-Fei Ren; Jiahui Shao (Water Research, 2025)

A stab-/solvent-resistant HAG/silicone armor for durably stretchable electroluminescent device - Jun-Yue Li; Xin-Kai Qian; Qi-Ye Wang; Hong-Chao Sun; Xiu-Juan Li; Zhen-Yu Zhang; Chao-Ran Huang; Rui Guo; Fei Xiu; Ju-Qing Liu (Chemical Engineering Journal, 2025)

Refined one-dimensional modeling and experimental validation of scroll compressor with vapor injection for electric vehicles - Kang Li; Jiayun Hu; Chao Li; Xuejin Zhou; Ni Liu; Hua Zhang; Binlin Dou; Qize He; Ran Tu; Lin Su; Soheil Mohtaram (International Journal of Refrigeration, 2024)

EDDS application destabilizes soil organic matter in phytoremediation: Insights from quantity and molecular composition of dissolved organic matter - Yan-ping Zhao; Peng-ran Guo; Zhi-liang Chen; Jin-li Cui; Jian-xu Wang; Chao Chen; Hang Wei; Cheng Wang (Environmental Research, 2024)

Analyzing performance and microbial mechanisms in an incineration leachate treatment after waste separation: Integrated metagenomic and metaproteomic analyses - Han Wang; Xiaoqian Ma; Xiaochuan Ran; Tong Wang; Mingda Zhou; Chao Liu; Xiang Li; Min Wu; Yayi Wang (Science of The Total Environment, 2024)

In situ iron coating of amorphous boron and characterization of its energy release behavior - Hongyang Li; Hong Li; Chao Wang; Zhenfeng Shen; Shentao Zeng; Sujun Shi; Qing Cai; Wenqi Xu; Ran Wang; Cui Luo; Ying Liu (Chemical Engineering Journal, 2024)

Charge transfer complex induced confinement effect between organic semiconductor and polymer chains for enhancing high-temperature capacitive energy storage - Tan Zeng; Chao Yuan; Qiao Li; Zhaoyu Ran; Li Meng; Jing Fu; Dongduan Liu; Jinliang He; Qi Li (Chemical Engineering Journal, 2024)

Novel visible-light activated photocatalytic ultrafiltration membrane for simultaneous separation and degradation of emerging contaminants - Ran Li; Zhidong Wei; Peng Li; Yangbo Qiu; Chengyi Wang; Chao Wang; Long-Fei Ren; Jiahui Shao; Yiliang He (Journal of Hazardous Materials, 2024)

Quantification of two-phase flow in a microchannel heat exchanger header based on capacitance measurement - Jiajia Song; Hequn Liu; Chao Yuan; Ran Wang; Jinqing Peng; Lizhi Wang; Haobo Jiang; Houpei Li (International Journal of Refrigeration, 2024)

Undervalued dry riverbeds: A key factor in equating intermittent river CO2 emissions to perennial rivers - Chao Qin; Yuan Xue; Mengzhen Xu; Lishan Ran; Dongfeng Li; Ge Wang; Defan Cun; Baosheng Wu; Xudong Fu; Guangqian Wang (Water Research, 2024)

Immobilization of Nickel- and Cobalt-Based Complexes in NH2-UiO-66 for Efficient CO2 Photoreduction - Yu Jiang; Si-Chao Liu; Li-Ping Zhang; Guo-Wei Guan; Yi-Tao Li; Shuang Ni; Run-Yuan Jiang; Su-Tao Zheng; Hao-Ran Liu; Hao-Ling Lan; Qing-Yuan Yang (Chemical Engineering Journal, 2024)

The fabrication of Mn single atoms/clusters on Al2O3 for enhanced catalytic NO oxidation - Xiao-Ke Hou; Hui-Xin Zhang; Yi-Bo Wang; Jin-Ping Zhang; Xin Gao; Lei Chen; Chao Li; Hong-Mei Jing; Chi He; Qiang Lu; Chun-Ran Chang (Fuel, 2024)

Novel electrocatalytic capacitive deionization with catalytic electrodes for selective phosphonate degradation: Performance and mechanism - Chengyi Wang; Siyue Xue; Yubo Xu; Ran Li; Yangbo Qiu; Chao Wang; Long-Fei Ren; Jiahui Shao (Water Research, 2024)

Mechanical protein polycystin-1 directly regulates osteoclastogenesis and bone resorption - Mei Huang; Jingxuan Zhou; Xiaoxiao Li; Ran Liu; Yangzi Jiang; Kaixuan Chen; Yurui Jiao; Xin Yin; Ling Liu; Yuchen Sun; Weishan Wang; Ye Xiao; et al. (Science Bulletin, 2024)

Enhancing anaerobic digestion of actual papermaking wastewater with addition of Fenton sludge - Xianbao Wang; Xiang Li; Yili Xie; Jialu Zhang; Jiarong Ran; Minting Zhang; Lixin Zhang; Anlong Zhang; Chao Zhu (Journal of Water Process Engineering, 2024)

Dietary Bacillus velezensis T23 fermented products supplementation improves growth, hepatopancreas and intestine health of Litopenaeus vannamei - Hongwei Yang; Dongdong Du; Qingshuang Zhang; Tsegay Teame; Anran Wang; Qiang Hao; Shubin Liu; Qianwen Ding; Yuanyuan Yao; Yalin Yang; Chao Ran; Shengkang Li; et al. (Fish & Shellfish Immunology, 2024)

Effects of dietary bacterial culture of fengycin-producing Bacillus subtilis on growth performance, intestinal and hepatopancreas health, intestinal microbiota and disease resistance of common carp (Cyprinus carpio) - Rui Xia; Shenghui Li; Hongwei Yang; Yajie Zhao; Tsegay Teame; Qiang Hao; Mingxu Xie; Min Li; Qile Chen; Chunling Song; Chao Ran; Yalin Yang; et al. (Aquaculture, 2024)

Spatial modelling of street-level carbon emissions with multi-source open data: A case study of Guangzhou - Yingsheng Zheng; Wenjie Li; Lu Jiang; Chao Yuan; Te Xiao; Ran Wang; Meng Cai; Haobin Hong (Urban Climate, 2024)

Macrophage AHR-TLR4 cross-talk drives p-STAT3 (Ser727)-mediated mitochondrial oxidative stress and upregulates IDO/ICAM-1 in the steatohepatitis induced by aflatoxin B1 - Jing Zhang; Hui Liu; Yang Shen; Dong Cheng; Hui Tang; Qi Zhang; Chao Li; Ming Liu; Wenhuan Yao; Rongrong Ran; Qingzhen Hou; Xiulan Zhao; et al. (Science of The Total Environment, 2024)

Antimony and arsenic migration in a heterogeneous subsurface at an abandoned antimony smelter under rainfall - Chao Li; Yiyuan Ran; Pan Wu; Peng Liu; Boyi Yang; Xueyuan Gu; Ping Zhao; Shirong Liu; Lei Song; Yuhui Liu; Yizhang Liu; Zengping Ning; et al. (Journal of Hazardous Materials, 2024)

Gut bacterial community and gene expression alterations induced by transgenic Bt maize contribute to insecticidal activity against Mythimna separata - Chao Xu; Junyu Luo; Li Wang; Xiangzhen Zhu; Hui Xue; Ningbo Huangfu; Xueke Gao; Dongyang Li; Kaixin Zhang; Ran Chen; Jichao Ji; Changying Niu; et al. (Journal of Pest Science, 2024)

Cover Image - Qingshuang Zhang; Hongwei Yang; Tsegay Teame; Chao Ran; Yalin Yang; Yuanyuan Yao; Qianwen Ding; Shubin Liu; Shengkang Li; Zhen Zhang; Zhigang Zhou (Reviews in Aquaculture, 2024)
The cover image is based on the Review Article Immune disorders induced by improper use of dietary immunostimulants in aquatic animals: Research progress and prospective solutions by targeting gut microbiota by Qingshuang Zhang and Hongwei Yang et al., https://doi.org/10.1111/raq.12852 . [Correction added on 27 March 2024, after first online publication: Cover image has been changed] image

Immune disorders induced by improper use of dietary immunostimulants in aquatic animals: Research progress and prospective solutions by targeting gut microbiota - Qingshuang Zhang; Hongwei Yang; Tsegay Teame; Chao Ran; Yalin Yang; Yuanyuan Yao; Qianwen Ding; Shubin Liu; Shengkang Li; Zhen Zhang; Zhigang Zhou (Reviews in Aquaculture, 2024)
Immunostimulants were widely used in aquafeed due to their multiple important functions, including promoting growth, enhancing non‐specific defence mechanisms and resisting infectious diseases. But the efficiencies of the positive effects of immunostimulants were affected by the duration of the administration and their dose. Short‐term and normal‐dose of immunostimulants promoted the growth and enhance non‐specific immunity of aquatic animals. However, improper use led to several immune disorders, including immune tolerance, immune exhaustion and over‐immunity. The application of two immunostimulant diets in rotation technique and the intermittent use of immune stimulant diets may solve the problems associated with immune disorders, but this application method will be limited by both species and immunostimulants. The occurrence of immune disorders is accompanied by different degrees of gut microbiota dysbiosis, especially significantly up‐regulated the abundance of Proteobacteria. Besides, the gut symbiotic microbiota plays a significant role in host immunity. Consequently, the regulation of gut microbiota may be an effective way to modulate immune disorders caused by improper use of polysaccharide immunostimulants. Regulating the gut microbiota not only solves the negative effects caused by improper use of immunostimulants without restrictions on both species and immunostimulants, but also has the advantage of simplicity and convenience compared to conventional approaches. In summary, this article reviews the possible negative effects caused by improper use of immunostimulants on aquatic animals and compares regular approaches with regulating gut microbiota. And gut microbiota maybe be used as a therapeutic target to improve immune disorders caused by immunostimulants in aquatic animals.

Leucine improves dietary protein use efficiency by regulating protein synthesis by activating amino acid transporters and the mTORC1 pathways in Chinese mitten crab (Eriocheir sinensis) - Ming-Qi Song; Qiu-Ran Yu; Er-Chao Li; Ying Song; Xin-Yu Cai; Yu-Xiang Huang; Chuan-Jie Qin; Xiao-Dan Wang; Jian-Guang Qin; Li-Qiao Chen (Aquaculture, 2024)

Environmental surveillance in Jinan city of East China (2014–2022) reveals improved air quality but remained health risks attributable to PM2.5-bound metal contaminants - Zhigang Yu; Zhan Sun; Lanzheng Liu; Chao Li; Xin Zhang; Gzalnur Amat; Mohan Ran; Xiaoyue Hu; Yunxiang Xu; Xiulan Zhao; Jun Zhou (Environmental Pollution, 2024)

Self-Assembled FeIII-TAML-Based Magnetic Nanostructures for Rapid and Sustainable Destruction of Bisphenol A - Ruochen Dong; Lihua Bai; Sijia Liang; Shuxia Xu; Song Gao; Hongjian Li; Ran Hong; Chao Wang; Cheng Gu (Bulletin of Environmental Contamination and Toxicology, 2024)

Effective electrosorption and recovery of phosphorus by capacitive deionization with a covalent organic framework-membrane coating electrode - Chengyi Wang; Ran Li; Yubo Xu; Zhongbao Ma; Yangbo Qiu; Chao Wang; Long-Fei Ren; Jiahui Shao (Desalination, 2024)

Dietary cultured supernatant mixture of Cetobacterium somerae and Lactococcus lactis improved liver and gut health, and gut microbiota homeostasis of zebrafish fed with high-fat diet - Shenghui Li; Hongwei Yang; Ya Jin; Qiang Hao; Shubin Liu; Qianwen Ding; Yuanyuan Yao; Yalin Yang; Chao Ran; Chenglong Wu; Shengkang Li; Kaimin Cheng; et al. (Fish & Shellfish Immunology, 2023)

Indoor exposure to polycyclic aromatic hydrocarbons associated with solid fuel use in rural China - Shiyin Li; Yatai Men; Zhihan Luo; Wenxuan Huang; Ran Xing; Chao Sun; Guofeng Shen (Environmental Geochemistry and Health, 2023)

The effect of stabilized culture of Lactobacillus rhamnosus GCC-3 on gut and liver health, and anti-viral immunity of zebrafish - Hui Liang; Yadong Xie; Ming Li; Jie Chen; Wenhao Zhou; Rui Xia; Qianwen Ding; Yuanyuan Yao; Zhen Zhang; Yalin Yang; Chao Ran; Zhigang Zhou (Fish & Shellfish Immunology, 2023)

Global prevalence and factors affecting the level of Cryptosporidium contamination in soil: A systematic review, meta-analysis, and meta-regression - Mu-Ran Zuo; Xiao-Ting Li; Rui-Zhe Xu; Wen-Chao Sun; Hany M. Elsheikha; Wei Cong (Science of The Total Environment, 2023)

A novel bacteriocin RSQ01 with antibacterial activity and its application and metabolomic mechanism in milk preservation - Yan-Mei Zhang; Lin-Yu Yang; Jian-Ping Ying; Chao-Min Fu; Gang Wu; Xiao-Ran Li; Qi-Lin Zhang (Food Control, 2023)

Quantifying the contribution of temperature, salinity, and climate change to sea level rise in the Pacific Ocean: 2005-2019 - Junlin Ran; Nengfang Chao; Lianzhe Yue; Gang Chen; Zhengtao Wang; Tangting Wu; Chengchun Li (Frontiers in Marine Science, 2023)
In recent decades, Pacific Ocean’s steric sea level anomaly (SSLA) has shown prominent patterns among global sea level variations. With ongoing global warming, the frequency and intensity of climate and sea level changes have increased, particularly in the tropical Pacific region. Therefore, it is crucial to comprehend the overall trends and mechanisms governing volumetric sea level changes in the Pacific. To accurately quantify the spatiotemporal evolution characteristics of density-driven sea level change in the Pacific Ocean (PO) from 2005 to 2019, we decomposed temperature and salinity into linear trends, interannual variations, seasonal variations, and residual terms using the STL (seasonal-trend decomposition based on loess) method. To evaluate the influence of ocean temperature, salinity, and climate change on density-driven sea level change and its underlying mechanisms, we decompose temperature as well as salinity changes through into the Heaving (vertical displacements of isopycnal surfaces) and Spicing (density-compensated temperature and salinity change) modes. The findings reveal an average steric sea level rise rate of 0.34 ± 0.16 mm/yr in the PO from 2005 to 2019. Thermosteric sea-level accounts for 82% of this rise, primarily due to seawater temperature rise at depths of 0-700 m caused by Heaving mode changes. Accelerated SSLA increase via the thermosteric effect has been connected to interactions between greater Ekman downwelling from surface winds, radiation forcing linked to global greenhouse gases, and changes in the Pacific warm currents triggered by El Niño-Southern Oscillation (ENSO) episodes. Although salinity is affected by the Subantarctic Mode Water (SAMW) and the Antarctic Intermediate Water (AAIW) in the southern Indian Ocean, however the significance of salinity in sea level change is little compared to the role played by thermocline shift. This study offers a substantial contribution to the field, providing robust data and technical support, and facilitating a deeper understanding of the mechanisms underlying the effects of temperature and salinity on sea level changes during periods of rapid climate change, thus enhancing the accuracy of future predictions regarding sea level rise.

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Migraine, chronic kidney disease and kidney function: observational and genetic analyses - Wenqiang Zhang; Li Zhang; Luo Yang; Chenghan Xiao; Xueyao Wu; Peijing Yan; Huijie Cui; Chao Yang; Jingwei Zhu; Xuan Wu; Mingshuang Tang; Yutong Wang; et al. (Human Genetics, 2023)
Epidemiological studies demonstrate an association between migraine and chronic kidney disease (CKD), while the genetic basis underlying the phenotypic association has not been investigated. We aimed to help avoid unnecessary interventions in individuals with migraine through the investigation of phenotypic and genetic relationships underlying migraine, CKD, and kidney function. We first evaluated phenotypic associations using observational data from UK Biobank ( N = 255,896). We then investigated genetic relationships leveraging genomic data in European ancestry for migraine ( N case / N control = 48,975/540,381), CKD ( N case / N control = 41,395/439,303), and two traits of kidney function (estimated glomerular filtration rate [eGFR, N = 567,460] and urinary albumin-to-creatinine ratio [UACR, N = 547,361]). Observational analyses suggested no significant association of migraine with the risk of CKD (HR = 1.13, 95% CI = 0.85–1.50). While we did not find any global genetic correlation in general, we identified four specific genomic regions showing significant for migraine with eGFR. Cross-trait meta-analysis identified one candidate causal variant (rs1047891) underlying migraine, CKD, and kidney function. Transcriptome-wide association study detected 28 shared expression–trait associations between migraine and kidney function. Mendelian randomization analysis suggested no causal effect of migraine on CKD (OR = 1.03, 95% CI = 0.98–1.09; P = 0.28). Despite a putative causal effect of migraine on an increased level of UACR (log-scale-beta = 0.02, 95% CI = 0.01–0.04; P = 1.92 × 10 −3 ), it attenuated to null when accounting for both correlated and uncorrelated pleiotropy. Our work does not find evidence supporting a causal association between migraine and CKD. However, our study highlights significant biological pleiotropy between migraine and kidney function. The value of a migraine prophylactic treatment for reducing future CKD in people with migraine is likely limited.

The positive effects of postbiotic (SWF concentration®) supplemented diet on skin mucus, liver, gut health, the structure and function of gut microbiota of common carp (Cyprinus carpio) fed with high-fat diet - Zhe Yu; Qiang Hao; Shu-Bin Liu; Qing-Shuang Zhang; Xing-Yu Chen; Sheng-Hui Li; Chao Ran; Ya-Lin Yang; Tsegay Teame; Zhen Zhang; Zhi-Gang Zhou (Fish & Shellfish Immunology, 2023)

Deep Sc-RNA sequencing decoding the molecular dynamic architecture of the human retina - Lulin Huang; Runze Li; Lin Ye; Shanshan Zhang; Huaping Tian; Mingyan Du; Chao Qu; Shujin Li; Jie Li; Mu Yang; Biao Wu; Ran Chen; et al. (Science China Life Sciences, 2023)

Soil Carbon Emission Sources Differ Under Litter and Nutrient Addition During Secondary Succession: Evidence from a Mesocosm Study Using a Three-Transfer-Pool Model - Tiantian Li; Cuijuan Liao; Chao Wang; Weiming Yan; Ran Sun; Yangquanwei Zhong (Journal of Soil Science and Plant Nutrition, 2023)

Crystal-modeler: A tool for geometric analysis and three-dimensional modeling of crystal forms based on rectangular coordinates in space - Huixia Chao; Yue Li; Weihua Yao; Xin Han; Ran Wang (Earth Science Informatics, 2023)

Legal advice on the Chinese compensatory fund system for oil pollution damage caused by ships from the perspective of marine environmental governance - Ben-Chao Fu; He-Ran Li (Frontiers in Marine Science, 2023)
As one of the primary obstructive factors for marine environmental governance, the frequent occurrence of oil pollution damage caused by ships has resulted in the establishment of compensation funds, such as the Oil Spill Liability Trust Fund of the United States, Ship Oil Pollution Fund of Canada and International Oil Pollution Compensation Fund (IOPC). Frequently suffering from marine oil pollution, China has extended considerable effort in marine environmental governance. Following the introduction of the ‘green principle’ into the Civil Code, China attached increasing significance to the legislation including compensation for oil pollution damage caused by ships. China formally established a compensation fund in 2012, and the past decade has witnessed the burgeoning development of the Chinese Ship-source Oil Pollution Compensation Fund (CSOPC), in addition to several defects which impede the fund from achieving the goal of marine environmental governance. As a national fund that is independent of the IOPC, the CSOPC adopts several regulations that are distinctive from internationally recognized practice; for instance, not recognizing pure economic loss within the scope of compensation. Such unique parameters, though partially originating from the national conditions in China, have resulted in glaring defects, including incomplete compensation scope and inappropriate compensation measures. Given the above problems, this study endeavours to provide several legal recommendations from the perspective of macro policies for improving the top-level design of the system, enhancing oil pollution compensation capabilities, and promoting the internationalization process. The study proposes two potential regulatory paths for innovation; namely, enlarging the range of compensation and establishing an essential emergency fund. From the perspective of protecting the rights of the victims of oil pollution damage and safeguarding the public interests of the ocean, this study puts forward relevant legal suggestions, which are expected to make valuable contributions to improving the compensation system for oil pollution damage caused by ships in China and promoting the governance of the marine environment.

Dietary supplementation of yeast mannan enhances antiviral immunity of zebrafish (Danio rerio) - Hui Liang; Yadong Xie; Yu Li; Mingxu Xie; Ming Li; Wei Zhou; Jie Chen; Zhen Zhang; Yalin Yang; Chao Ran; Zhigang Zhou (Aquaculture, 2023)

Azospirillum Endophyticum sp. nov., an Endophyte of Paris Polyphylla Smith var. Yunnanensis - Peng-Chao Zhan; Rui-Feng Mao; Cong-Jian Li; Zhen Zhang; Jing-Ran Liu; Mei Tang; Xiao-Yang Zhi; Ling-Ling Yang (Current Microbiology, 2023)

Testing the isotopic equilibrium fractionation on active speleothem based on cave monitoring - Yang-Yang Huang; Ting-Yong Li; Chao-Jun Chen; Ran Huang; Tao Wang; Yao Wu; Si-Ya Xiao; Yu-Zhen Xu; Hai-Ying Qiu; Yan Yang; Jun-Yun Li (Journal of Earth System Science, 2022)

Exogenous artificial DNA forms chromatin structure with active transcription in yeast - Jianting Zhou; Chao Zhang; Ran Wei; Mingzhe Han; Songduo Wang; Kaiguang Yang; Lihua Zhang; Weigang Chen; Mingzhang Wen; Cheng Li; Wei Tao; Ying-Jin Yuan (Science China Life Sciences, 2022)
Yeast artificial chromosomes (YACs) are important tools for sequencing, gene cloning, and transferring large quantities of genetic information. However, the structure and activity of YAC chromatin, as well as the unintended impacts of introducing foreign DNA sequences on DNA-associated biochemical events, have not been widely explored. Here, we showed that abundant genetic elements like TATA box and transcription factor-binding motifs occurred unintentionally in a previously reported data-carrying chromosome (dChr). In addition, we used state-of-the-art sequencing technologies to comprehensively profile the genetic, epigenetic, transcriptional, and proteomic characteristics of the exogenous dChr. We found that the data-carrying DNA formed active chromatin with high chromatin accessibility and H3K4 tri-methylation levels. The dChr also displayed highly pervasive transcriptional ability and transcribed hundreds of noncoding RNAs. The results demonstrated that exogenous artificial chromosomes formed chromatin structures and did not remain as naked or loose plasmids. A better understanding of the YAC chromatin nature will improve our ability to design better data-storage chromosomes.

Seepage field distribution and water inflow laws of tunnels in water-rich regions - Zheng Li; Zi-quan Chen; Chuan He; Chun-chi Ma; Chao-ran Duan (Journal of Mountain Science, 2022)

Neobacillus paridis sp. nov., an endophyte of Paris polyphylla Smith var. yunnanensis - Peng-Chao Zhan; Cong-Jian Li; Zhen Zhang; Rui-Feng Mao; Jing-Ran Liu; Xing-Wang Jiang; Xiao-Yang Zhi; Ling-Ling Yang (Archives of Microbiology, 2022)

An atlas of CNV maps in cattle, goat and sheep - Yongzhen Huang; Yunjia Li; Xihong Wang; Jiantao Yu; Yudong Cai; Zhuqing Zheng; Ran Li; Shunjin Zhang; Ningbo Chen; Hojjat Asadollahpour Nanaei; Quratulain Hanif; Qiuming Chen; et al. (Science China Life Sciences, 2021)

Interactions between commensal bacteria and viral infection: insights for viral disease control in farmed animals - Chao Ran; Yu Li; Xufa Ma; Yadong Xie; Mingxu Xie; Yuting Zhang; Wei Zhou; Yalin Yang; Zhen Zhang; Li Zhou; Kaijian Wei; Zhigang Zhou (Science China Life Sciences, 2021)

Prediction of methane production from co-digestion of lignocellulosic biomass with sludge based on the major compositions of lignocellulosic biomass - Pengfei Li; Chao He; Chongbo Cheng; Youzhou Jiao; Dekui Shen; Ran Yu (Environmental Science and Pollution Research, 2021)

Evaluation of the stability of vegetated slopes according to layout and temporal changes - Yun-peng Li; Chao Hu; Li Jian; Ran Zhao; Chen Li (Journal of Mountain Science, 2021)

Surface display system for probiotics and its application in aquaculture - Yuan‐Yuan Yao; Ya‐Lin Yang; Chen‐Chen Gao; Feng‐Li Zhang; Rui Xia; Dong Li; Juan Hu; Chao Ran; Zhen Zhang; Jihong Liu‐Clarke; Zhi‐Gang Zhou (Reviews in Aquaculture, 2020)
Aquaculture is a fast‐growing and rapidly expanding industry in the world. Probiotics are widely used in aquaculture and have provided benefits to aquatic animal health, and it is also a promising alternative to antibiotics for control of fish diseases. With the development of biotechnology, new expression systems and novel techniques for the surface display of heterologous proteins in surface of probiotics cells have been developed. This review provides an overview of the systems and strategies for displaying functional proteins on the surface of probiotics commonly used in aquaculture, which are Bacillus subtilis , Bacillus thuringiensis , lactic acid bacteria represented by Lactococcus lactis and yeast. Their applications in aquaculture especially for oral vaccine development afforded by this technology and prospects and challenges associated with this technology are also highlighted.

Combining DC-GAN with ResNet for blood cell image classification - Li Ma; Renjun Shuai; Xuming Ran; Wenjia Liu; Chao Ye (Medical & Biological Engineering & Computing, 2020)

Effects of different green manure treatments on soil apparent N and P balance under a 34-year double-rice cropping system - Xi Hong; Chao Ma; Jusheng Gao; Shiming Su; Tao Li; Zunchang Luo; Ran Duan; Yanan Wang; Lingyu Bai; Xibai Zeng (Journal of Soils and Sediments, 2019)

Aeromonas veronii and aerolysin are important for the pathogenesis of motile aeromonad septicemia in cyprinid fish - Chao Ran; Chubin Qin; Mingxu Xie; Jinxiong Zhang; Jie Li; Yadong Xie; Yibing Wang; Shuning Li; Lihui Liu; Xiaozhe Fu; Qiang Lin; Ningqiu Li; et al. (Environmental Microbiology, 2018)
Summary Aeromonas species are ubiquitous inhabitants of freshwater environments, and are responsible for fish motile aeromonad septicemia (MAS). A. hydrophila is implicated as the primary etiologic agent of MAS. Here, we analysed MAS epidemiological data for cyprinid fish in southern China, and found that A. veronii infections dominated. Consistent with this observation, A. veronii isolates were generally more virulent than A. hydrophila isolates when infecting germ‐free zebrafish larvae via continuous immersion challenge. Through in vivo screening of the transposon library of the A. veronii strain Hm091, aerolysin was identified as the key virulence factor. Further results indicated that A. veronii Hm091 aerolysin disrupts the intestinal barrier of zebrafish, enabling systematic invasion by not only A. veronii Hm091 in a mono‐infection, but also A. hydrophila NJ‐1 in a mixed infection. Moreover, the differences in aerolysin expression and activity were the major contributor to the observed differences between the A. veronii and A. hydrophila strains regarding invasion efficacy via intestine. Together, our results provide new insights into the aetiology and pathogenesis of Aeromonas infections, and highlight the importance of A. veronii ‐targeted treatments in future efforts against MAS.

Correction to: In Vitro-In Vivo Dose Response of Ursolic Acid, Sulforaphane, PEITC, and Curcumin in Cancer Prevention - Christina N. Ramirez; Wenji Li; Chengyue Zhang; Renyi Wu; Shan Su; Chao Wang; Linbo Gao; Ran Yin; Ah-Ng Tony Kong (The AAPS Journal, 2018)

Identifying a Major QTL Associated with Salinity Tolerance in Nile Tilapia Using QTL-Seq - Xiao Hui Gu; Dan Li Jiang; Yan Huang; Bi Jun Li; Chao Hao Chen; Hao Ran Lin; Jun Hong Xia (Marine Biotechnology, 2018)

In Vitro-In Vivo Dose Response of Ursolic Acid, Sulforaphane, PEITC, and Curcumin in Cancer Prevention - Christina N. Ramirez; Wenji Li; Chengyue Zhang; Renyi Wu; Shan Su; Chao Wang; Linbo Gao; Ran Yin; Ah-Ng Kong (The AAPS Journal, 2018)

A novel missense mutation of $$ADAR1$$ ADAR 1 gene in a Chinese family leading to dyschromatosis symmetrica hereditaria and literature review - Shuai-Mei Liu; Meng-Xia Ni; Ming-Chao Zhang; Pei-Ran Zhu; Qiu-Yu Wu; Wei-Jun Jiang; Jing Zhang; Wei-Wei Li; Xin-Yi Xia (Journal of Genetics, 2017)

Antibiotic growth promoter olaquindox increases pathogen susceptibility in fish by inducing gut microbiota dysbiosis - Suxu He; Quanmin Wang; Shuning Li; Chao Ran; Xiaoze Guo; Zhen Zhang; Zhigang Zhou (Science China Life Sciences, 2017)

Genome-Wide QTL Analysis Identified Significant Associations Between Hypoxia Tolerance and Mutations in the GPR132 and ABCG4 Genes in Nile Tilapia - Hong Lian Li; Xiao Hui Gu; Bi Jun Li; Chao Hao Chen; Hao Ran Lin; Jun Hong Xia (Marine Biotechnology, 2017)

Trans-ethnic fine-mapping of genetic loci for body mass index in the diverse ancestral populations of the Population Architecture using Genomics and Epidemiology (PAGE) Study reveals evidence for multiple signals at established loci - Lindsay Fernández-Rhodes; Jian Gong; Jeffrey Haessler; Nora Franceschini; Mariaelisa Graff; Katherine K. Nishimura; Yujie Wang; Heather M. Highland; Sachiko Yoneyama; William S. Bush; Robert Goodloe; Marylyn D. Ritchie; et al. (Human Genetics, 2017)

NLRP3 is Required for Complement-Mediated Caspase-1 and IL-1beta Activation in ICH - Sheng-Tao Yao; Fang Cao; Jia-Lin Chen; Wei Chen; Rui-Ming Fan; Gang Li; You-Chao Zeng; Song Jiao; Xiang-Ping Xia; Chong Han; Qi-Shan Ran (Journal of Molecular Neuroscience, 2017)

MicroRNA-99a regulates early chondrogenic differentiation of rat mesenchymal stem cells by targeting the BMPR2 gene - Xiaozhong Zhou; Jing Wang; Hongtao Sun; Yong Qi; Wangyang Xu; Dixin Luo; Xunjie Jin; Chao Li; Weijian Chen; Zhousheng Lin; Feimeng Li; Ran Zhang; et al. (Cell and Tissue Research, 2016)

Methane and nitrous oxide emissions under no‐till farming in China: a meta‐analysis - Xin Zhao; Sheng‐Li Liu; Chao Pu; Xiang‐Qian Zhang; Jian‐Fu Xue; Ran Zhang; Yu‐Qiao Wang; Rattan Lal; Hai‐Lin Zhang; Fu Chen (Global Change Biology, 2016)
No‐till ( NT ) practices are among promising options toward adaptation and mitigation of climate change. However, the mitigation effectiveness of NT depends not only on its carbon sequestration potential but also on soil‐derived CH 4 and N 2 O emissions. A meta‐analysis was conducted, using a dataset involving 136 comparisons from 39 studies in China, to identify site‐specific factors which influence CH 4 emission, CH 4 uptake, and N 2 O emission under NT . Comparative treatments involved NT without residue retention ( NT 0), NT with residue retention ( NTR ), compared to plow tillage ( PT ) with residue removed ( PT 0). Overall, NT 0 significantly decreased CH 4 emission by ~30% ( P 0.05) compared to PT 0 with an average emission 218.8 kg ha −1 for rice paddies. However, the increase in N 2 O emission could partly offset the benefits of the decrease in CH 4 emission under NT compared to PT 0. NTR significantly enhanced N 2 O emission by 82.1%, 25.5%, and 20.8% ( P 0.05) compared to PT 0 for rice paddies, acid soils, and the first 5 years of the experiments, respectively. The results from categorical meta‐analysis indicated that the higher N 2 O emission could be mitigated by adopting NT within alkaline soils, for long‐term duration, and with less N fertilization input when compared to PT 0. In addition, the natural log (lnR) of response ratio of CH 4 and N 2 O emissions under NT correlated positively (enhancing emission) with climate factors (temperature and precipitation) and negatively (reducing emission) with experimental duration, suggesting that avoiding excess soil wetness and using NT for a long term could enhance the benefits of NT . Therefore, a thorough understanding of the conditions favoring greenhouse gas(es) reductions is essential to achieving climate change mitigation and advancing food security in China.

PPR protein PDM1/SEL1 is involved in RNA editing and splicing of plastid genes in Arabidopsis thaliana - Hong-Dao Zhang; Yong-Lan Cui; Chao Huang; Qian-Qian Yin; Xue-Mei Qin; Te Xu; Xiao-Fang He; Yi Zhang; Zi-Ran Li; Zhong-Nan Yang (Photosynthesis Research, 2015)

Wild soybean roots depend on specific transcription factors and oxidation reduction related genesin response to alkaline stress - Huizi DuanMu; Yang Wang; Xi Bai; Shufei Cheng; Michael K. Deyholos; Gane Ka-Shu Wong; Dan Li; Dan Zhu; Ran Li; Yang Yu; Lei Cao; Chao Chen; et al. (Functional & Integrative Genomics, 2015)

Modeling and optimization of the flocculation processes for removal of cationic and anionic dyes from water by an amphoteric grafting chitosan-based flocculant using response surface methodology - Hu Wu; Ran Yang; Ruihua Li; Chao Long; Hu Yang; Aimin Li (Environmental Science and Pollution Research, 2015)

Recycling of sediment into the mantle source of K-rich mafic rocks: Sr–Nd–Hf–O isotopic evidence from the Fushui complex in the Qinling orogen - Hao Wang; Yuan-Bao Wu; Chao-Ran Li; Tian-Yu Zhao; Zheng-Wei Qin; Liu-Qin Zhu; Shan Gao; Jian-Ping Zheng; Xiao-Ming Liu; Lian Zhou; Yang Zhang; Sai-Hong Yang (Contributions to Mineralogy and Petrology, 2014)

Subaquatic volcanic eruptions in continental facies and their influence on high quality source rocks shown by the volcanic rocks of a faulted depression in Northeast China - XuanLong Shan; JiYan Li; ShuMin Chen; QingChang Ran; GuiBiao Chen; Chao Liu (Science China Earth Sciences, 2013)

Continuous evolution of avian infectious bronchitis virus resulting in different variants co-circulating in southern China - Meng Li; Mei-Lan Mo; Bai-Cheng Huang; Wen-Sheng Fan; Zheng-Ji Wei; Tian-Chao Wei; Kang-Ran Li; Ping Wei (Archives of Virology, 2013)

Polybrominated diphenyl ethers in background surface soils from the Yangtze River Delta (YRD), China: occurrence, sources, and inventory - Yan-Ping Duan; Xiang-Zhou Meng; Chao Yang; Zhao-Yu Pan; Ling Chen; Ran Yu; Feng-Ting Li (Environmental Science and Pollution Research, 2010)

MicroRNA-128 inhibits glioma cells proliferation by targeting transcription factor E2F3a - Yu Zhang; Tengfei Chao; Ran Li; Wei Liu; Yang Chen; Xingqi Yan; Yanhua Gong; Bin Yin; Wei Liu; Boqing Qiang; Jizhong Zhao; Jiangang Yuan; et al. (Journal of Molecular Medicine, 2009)

TM4SF3 promotes esophageal carcinoma metastasis via upregulating ADAM12m expression - Zhuan Zhou; Yu-Liang Ran; Hai Hu; Jian Pan; Zhi-Feng Li; Li-Zhao Chen; Li-Chao Sun; Liang Peng; Xi-Lu Zhao; Long Yu; Li-Xin Sun; Zhi-Hua Yang (Clinical & Experimental Metastasis, 2008)